Detection and characterization of enterocin encoding genes in enterococcus mundtii strain C4L10 from the cecum of non-broiler chicken - Alhaji Yusuf, Moshood; Tengku Abdul Hamid, Tengku Haziyamin (IJPPS, 2015)
This study was carried out to isolate and detect the enterocin genes of the bacteriocin producing strain Enterococcus mundtii C4L10 isolated from Malaysian non-broiler chicken. Amplified bacteriocin encoding genes were extracted from the total genome of Enterococcus mundtii strain C4L10 using specific sets of primers. The translated protein of the resultant enterocin gene sequence showed that the bacteriocin contain 2 sets of Enterocins; Enterocin_P and Enterocin_B. The enterocin gene was found to be located in the chromosome. The bacteriocin of C4L10 has a molecular mass of approximately 10 kDa. At the amino acid level, bacteriocin of strain C4L10 is 85% homologous to enterocin_P which is similar to class IIa bacteriocins produced by Lactoctobacillus salivarius strain. The secondary structure prediction showed that the Enterocin_P contain double glycine motifs and YGNGP instead of the normal YGNGV characteristics of class IIa bacteriocin. Conserved domain search of the encoding gene revealed the presence of Glycosyltransferases domain in the Enterocin_B. The antimicrobial spot/region of the C4L10 enerocins showed the presence of two antimicrobial regions in Enterocin_P whereas only one antimicrobial spot was detected in Enterocin_B. In this study, two enterocin genes; enterocin_P and Enterocin_B were successfully amplified and characterised from Ent. Mundtii strain C4L10. The sequences showed strong similarity with reported class IIa bacteriocin, such as having double glycine and YGNGV motifs, and potential regions with antimicrobials activities which are useful for future exploitation in rational design of antimicrobial peptides.